Carrier Transport in Multi Colour Deep Ultraviolet Light Emitting Diodes - Hofmann, Gregor; Höpfner, J.; Schilling, M.; Muhin, A.; Romer, F.; Wernicke, T.; Kneissl, M.; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2022)
Deep ultraviolet (DUV) light emitting diodes (LEDs) and lasers are enabled by high band gap Aluminium Gallium Nitride (AlGaN). The efficiency of recent multi quantum well (MQW) DUV emitters is still in the percent range which can be in part attributed to the hole injection. The hole injection and the carrier distribution in the high band gap AlGaN active region are not yet well understood. To support the experimental investigation of the current injection and distribution we have performed numerical simulations of a mixed MQW DUV LED series emitting at 233nm and 250 nm. We demonstrate that particularly the emission of the 233nm quantum well is very sensitive to the AlGaN material properties and inhomogeneous broadening. The numerical modelling enables a better interpretation of experimental data.
CRIS-Team Scopus Importer:2022-10-21